Market competition in European hospital care - NORMAND, CHARLES (World Health Organisation, 2009)
This chapter investigates some elements of market competition in European hospital care. We use the term market competition as a broad concept, covering a diverse and hard to demarcate range of changes or reforms, such as the growth of the profi t-making market, the rise of private entrants in hospital care, or the introduction of new models for hospital funding that seek better to relate payment to performance.
PUBLISHED
Keywords: Public Health & Primary Care